Meta-analysis of traditional herbal medicine in the treatment of nonalcoholic fatty liver disease - Peng, H; He, Y; Zheng, G; Zhang, W; Yao, Z; Xie, W (Cellular and Molecular Biology, 2016)
Traditional Chinese herbal medicine (TCM) has been found effective for nonalcoholic fatty liver disease (NAFLD) based on its unique theory system and substantial herb remedies. The aim of this meta-analysis was to evaluate the efficiency and safety of one of the TCM, Danshen in the treatment of NAFLD. Seven English and Chinese databases were searched from inceptions to December 2015. RCTs which compared Danshen with placebo in adult patients with NAFLD were included. Totally, 8 RCTs with a total of 800 patients were identified. The results showed that compared with placebo, Danshen had increased total effectiveness rate, lower level of ALT, AST, TC and TG, LDL and higher level of liver/spleen computed tomography ratio. The present meta-analysis suggests that Danshen may have positive effects on nonalcoholic fatty liver disease. Future multicenter large-sample randomized clinical trials are still needed to confirm the efficacy and safety of our study.